Naringin targets Zeb1 to suppress osteosarcoma cell proliferation and metastasis - Ming, He (Aging (Albany NY), 2018)
Naringin, a citrus bioflavonoid, has anti-inflammatory actions and cardio- and neuroprotective effects. In addition, naringin exhibits multiple antitumor actions in several cancer types, including osteosarcoma, the most common type of bone cancer. Here, we show that naringin inhibits proliferation and invasion and induces apoptosis in human osteosarcoma cells by inhibiting zinc finger E-box binding homeobox 1 (Zeb1), a transcriptional repressor of epithelial differentiation involved in tumor metastasis. Our expression analyses confirm that Zeb1 is highly expressed in osteosarcoma specimens and cell lines. The effects of naringin, which included downregulation of Cyclin D1, MMP2, and bcl-2, where reproduced by siRNA-mediated Zeb1 silencing, whereas Zeb1 overexpression increased proliferation, migration, and Cyclin D1, MMP2, and bcl-2 levels. In addition, naringin administration reduced tumor nodule formation and attenuated the expression of the above proteins in the livers of mice injected with MG63 osteosarcoma cells. Our study provides preclinical evidence for the potential therapeutic application of naringin in the treatment of osteosarcoma.